Analytic geometry - Montero-Galliguez, Thelma C.; Gaquing, Jr., Napoleon A.;Lopez-Conde, Rosie C.;Abao, Zenon R. (Quezon City, Philippines : C & E Publishing Inc., 2015)
This book is intended for a one-semester freshman-level course in analytic geometry primarily for students with majors in the sciences, engineering, mathematics, and mathematics education. The books covers the prescribes material in accordance with the minimum standards prescribed by the Commission of Higher education (CHED) for engineering and mathematics education curricula.
Chapter 1. Inequalities and functions -- Chapter 2. Lines in two-dimensional space -- Chapter 3. Conics in rectangular coordinates -- Chapter 4. Transformation of axes -- Chapter 5.Equations in polar coordinates -- Chapter 6. Vectors in the plane -- Chapter 7. Vectors in three-dimensional space -- Chapter 8. Solid analytic geometry.
Includes bibliographical references.
Keywords: ANALYTICS -- GEOMETRY -- MATHEMATICS